Coronary artery bypass surgery in patients with severe left ventricular dysfunction - ARSAN, SİNAN (My University, 2003)
OBJECTIVE: The role of coronary artery bypass grafting (CABG) in patients with severe left ventricular dysfunction was evaluated. METHODS: Two hundred and twelve patients (152 men, 60 women; age 35 to 82, mean 55) with ejection fraction (EF) of less than 30% underwent CABG between January 1996 and February 2001 by a single surgeon (SA). They compromised of 12% of 1759 patients operated on in this period. EF ranged from 17% to 30% (mean 25%). Preoperatively 68% had congestive heart failure and 72% had severe angina (CCS 3 or 4). A left main lesion was found in 26% of the cases. The mean number of grafts was 3.18 per patient. The left internal mammary artery (LIMA) was used on 107 patients (50.4%). Preoperative intraaortic balloon pump (IABP) was used on 32 patients (15%). Endarterectomy was performed on 53 patients (25%). The patients were followed for up to 58 months (mean 28.7). RESULTS: Twelve patients died in hospital (5.6%). Survival was 94%, 87%, 80% and 73% at 1, 2, 3 and 4 years respectively. Among the preoperative variables survival was negatively affected by chronic renal failure, older age, congestive heart failure, elevated pulmonary artery pressure and recent myocardial infarction, by means of multivariate analysis. Preoperative IABP support improved the operative mortality significantly (P=0.002). Use of LIMA did not have any influence on survival. CONCLUSION: CABG on patients with poor left ventricular function: (1). Can be performed with an acceptable mortality. (2). Mid term results are encouraging. (3). Preoperative IABP support improves the chance of survival.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Aged; Aged, 80 and over; Male; Retrospective Studies; Chi-Square Distribution; Survival Rate; Ventricular Dysfunction, Left; Coronary Artery Bypass; Proportional Hazards Models